Wellbeing dynamics of migrant adolescents: Role of teachers and school as a context - Aalto, Sanni (fi=Turun yliopisto|en=University of Turku|, 2025)
Migrant adolescents often experience elevated levels of mental health difficulties, but also notable resilience. As a primary developmental context, school provides a crucial setting for promoting adaptation and wellbeing, with teachers serving a central role. Psychosocial, multi-tiered school interventions demonstrate potential for providing both universal and targeted student support. This thesis examined wellbeing profiles and their determinants among immigrant and refugee adolescents, as well as the association of teachers’ multicultural attitudes on their self-efficacy and wellbeing. It also presents the protocol and effectiveness study of two psychosocial school interventions aimed at enhancing migrant adolescents’ wellbeing. The findings are discussed through ecological, acculturation, and resilience frameworks. The data of this thesis derives from the RefugeesWellSchool project, a European collaboration across six countries examining psychosocial school interventions for migrant student wellbeing. Students and teachers completed self-report surveys at baseline, post-intervention, and follow-up. This thesis employed cross-sectional data from 1607 migrant students and 433 teachers across all countries, and longitudinal Finnish data from 1974 native and migrant students. Four wellbeing profiles emerged among migrant students, differing especially in PTSD symptom patterns. Refugee background, older age, discrimination, daily stress, and low family support were linked to profiles with poorer mental health. Among teachers, positive multicultural attitudes associated with greater work dedication, but not with work exhaustion. Self-efficacy mediated the association between multicultural attitudes and work-related wellbeing. Finally, the psychosocial interventions were generally not effective in increasing wellbeing; their benefits varied by students’ age, gender, and exposure to stress and discrimination. This thesis deepens understanding of migrant adolescents’ wellbeing, highlighting how individual and contextual factors shape both wellbeing and intervention outcomes. It also emphasizes teachers’ multicultural attitudes as important to both their wellbeing and efficacy beliefs. Overall, this doctoral thesis advocates for multidimensional, culturally informed collaboration across education, mental health, and social systems to better support migrant youth.

Maahanmuuttajanuorten hyvinvoinnin dynamiikka – Opettajien rooli ja koulu kontekstina Maahanmuuttajanuoret kokevat usein kohonneita mielenterveyden haasteita, mutta osoittavat myös merkittävää resilienssiä. Koulu tarjoaa tärkeän kontekstin nuorten ja hyvinvoinnin tukemiseen, ja opettajilla on tässä keskeinen rooli. Monitasoiset psykososiaaliset kouluinterventiot ovat osoittautuneet lupaaviksi tuen tarjoamisessa. Tämä väitöskirja tarkasteli maahanmuuttajanuorten hyvinvointiprofiileja ja niiden taustatekijöitä sekä opettajien monikulttuurisuusasenteiden, minäpystyvyyden ja hyvinvoinnin yhteyttä. Lisäksi esitellään kahden psykososiaalisen kouluintervention tutkimusprotokolla ja vaikuttavuustutkimus. Tuloksia tarkastellaan ekologisten, akkulturaatio- ja resilienssiteorioiden viitekehysten kautta. Väitöskirjan aineisto perustuu RefugeesWellSchool-hankkeeseen, joka oli kuuden Euroopan maan välinen yhteistyöhanke maahanmuuttajaoppilaiden hyvinvointia tukevien psykososiaalisten kouluinterventioiden tutkimiseksi. Oppilaat ja opettajat täyttivät itsearviointikyselyt tutkimuksen alku-, loppu- ja seurantavaiheessa. Työssä hyödynnettiin kaikkien maiden poikkileikkausaineistoa maahanmuuttajaoppilailta (n = 1607) ja opettajilta (n = 433) sekä Suomessa kerättyä pitkittäisaineistoa kantaväestön ja maahanmuuttajaoppilailta (n = 1974). Maahanmuuttajaoppilailla tunnistettiin neljä hyvinvointiprofiilia, jotka erosivat toisistaan erityisesti PTSD -oireiden suhteen. Pakolaistausta, syrjintäkokemukset, arjen stressitekijät ja heikko perheen tuki liittyivät heikompaan mielenterveyteen. Opettajien osalta monikulttuurisuusasenteet olivat yhteydessä vahvempaan työlle omistautumiseen, mutta eivät vähäisempään työuupumukseen. Minäpystyvyys välitti yhteyttä monikulttuurisuusasenteiden ja työhyvinvoinnin välillä. Psykososiaaliset interventiot eivät yleisesti lisänneet hyvinvointia, vaan niiden hyöty riippui oppilaiden iästä, sukupuolesta sekä stressi- ja syrjintäkokemuksista. Tämä väitöskirja korostaa yksilöllisten ja kontekstuaalisten tekijöiden vaikutusta maahanmuuttajanuorten hyvinvoinnille ja interventioiden vaikuttavuudelle. Lisäksi se painottaa opettajien monikulttuurisuusasenteiden merkitystä niin heidän omalle hyvinvoinnilleen kuin pystyvyyden kokemuksilleen. Kokonaisuudessaan väitöskirja suosittaa moniulotteista, kulttuurisensitiivistä yhteistyötä koulu-, mielenterveys- ja sosiaalipalveluiden välillä maahanmuuttajanuorten tukemisen edistämiseksi.